Efficacy of high magnification chromoscopic colonoscopy for the diagnosis of neoplasia in flat and depressed lesions of the colorectum: a prospective analysis. Issue 2 (14th January 2004) - Hurlstone, D P; Cross, S S; Adam, I; Shorthouse, A J; Brown, S; Sanders, D S; Lobo, A J
Abstract : Background: High magnification chromoscopic colonoscopy (HMCC) permits the in vivo examination of the colorectal pit pattern, which has a high correlation with stereomicroscopic appearances of resected specimens. This new technology may provide an "optical biopsy" which can be used to aid diagnostic precision and guide therapeutic strategies. Conflicting data exist concerning the accuracy of this technique when discriminating neoplastic from non-neoplastic lesions, particularly when flat and depressed. Aim: To prospectively examine the efficacy of HMCC for the diagnosis of neoplasia in flat and depressed colorectal lesions using standardised morphological, pit pattern, and histopathological criteria. Clinical recommendations for the use of HMCC are made. Methods: Total colonoscopy was performed on 1850 patients by a single endoscopist from January 2001 to July 2003 using the C240Z magnifying colonoscope. Identified lesions were classed according to the Japanese Research Society guidelines, and pit pattern according to Kudos modified criteria. Pit pattern appearances were then compared with histopathology. Results: A total of 1008 flat lesions were identified. The sensitivity and specificity of HMCC in distinguishing non-neoplastic from neoplastic lesions were 98% and 92%, respectively. However, when using HMCC to differentiate neoplastic/non-invasive from neoplastic/invasive lesions, sensitivity was poor (50%) with a specificity of 98%. Diagnostic accuracy was not influenced by size or morphological classification of lesions. Conclusion: HMCC has a high overall accuracy at discriminating neoplastic from non-neoplastic lesions but is not 100% accurate. HMCC is a useful diagnostic tool in vivo but presently is not a replacement for histology. Requirements for further education and training in these techniques need to be addressed.